PENGARUH GAYA KEPEMIMPINAN SITUASIONAL DAN KOMUNIKASI TERHADAP KEPUASAN KERJA KARYAWAN PADA CV SENI ECHO KEROBOKAN BALI - Mutria Farhaeni; Luh Kadek Budi Martini; I Wayan Astawa (Journal of Applied Management Studies, 2021)
This research aims to determine the influence of situational leadership style and communication to employee satisfaction at Cv. Seni Echo Kerobokan Bali which is located at Jalan Raya Padang No. 18, Kerobokan, Bali. This research was conducted on employees of Cv. Art Echo Kerobokan Bali amounting to 80 employees. Sampling using census methods. The analysis tool used is a double linear regression analysis. The results showed that the variables of the situational leadership style were positively and significantly important to employee work satisfaction and the communication variables also positively and significantly impact on employee work satisfaction. As for the large variable influence situational leadership style and communication to the employee's work satisfaction variable is 88.20%. The remaining 11.80% (100%-88.20%) Described by other factors not included in this study.